2010
DOI: 10.1080/01411920902919265
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous production of educational achievement and popularity: How do some pupils accomplish it?

Abstract: In spite of research showing that pupils—particularly boys—tend to experience tension between high academic achievement and popularity with peers at school, some pupils continue to maintain simultaneous production of both. This article focuses on a sample of 12–13 year‐old pupils, identified as high achieving and popular, to examine classroom subjectivities, with attention to their practices around gender and educational achievement. Data are drawn from a qualitative study funded by the Economic and Social Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(163 citation statements)
references
References 41 publications
7
133
1
13
Order By: Relevance
“…Ook interessant zijn de onderzoe-ken waarin wordt nagegaan waarom het sommige jongens en meisjes wel lukt om tegelijkertijd populair te zijn en ook schoolsucces te hebben (o.a. Francis, Skelton & Read, 2010). Dat blijkt onder meer samen te hangen met fysieke kenmerken: leerlingen met een aantrekkelijk uiterlijk en jongens die goed zijn in sport, slagen er beter in sociaal en academisch succes te combineren dan anderen.…”
Section: 'Peers'unclassified
See 1 more Smart Citation
“…Ook interessant zijn de onderzoe-ken waarin wordt nagegaan waarom het sommige jongens en meisjes wel lukt om tegelijkertijd populair te zijn en ook schoolsucces te hebben (o.a. Francis, Skelton & Read, 2010). Dat blijkt onder meer samen te hangen met fysieke kenmerken: leerlingen met een aantrekkelijk uiterlijk en jongens die goed zijn in sport, slagen er beter in sociaal en academisch succes te combineren dan anderen.…”
Section: 'Peers'unclassified
“…Vanuit Groot-Brittannië sloeg de paniek over naar andere landen (Francis, Skelton & Read, 2010). In de Verenigde Staten is sinds eind jaren negentig een reeks -veelal populair-, dan wel quasi-wetenschappelijke -boeken over dit onderwerp gepubliceerd.…”
Section: Introductieunclassified
“…The girls' science-related aspirations could be regarded as motivated by caring for and helping others, which research has previously found to be a strong motivator for many girls' career aspirations [36,92]. The link between healthcare and femininity has also been discussed elsewhere [93,94], with care being integral to dominant constructions of femininity [53,[95][96][97]. According to Skeggs [98], the centrality of care could be interpreted as having particular importance for girls/women from working-class backgrounds, who are constructed as needing to prove their respectability through caring performances.…”
Section: -Rifat (Interview June 2015)mentioning
confidence: 99%
“…For example, intensive and systematic work with reading and language development in primary schools is beneficial for boys because when they generally perform poorer in this area (Autor et al, 2016). Furthermore, there are a connection between learning and secure relationships, where security and a tolerant classroom climate create supportive conditions for the students' learning, a context that is particularly prominent when the students are younger, such as in primary school, and particularly for boys (Francis, Skelton & Read, 2010;Patrick, Kaplan, & Ryan, 2011). Competing and avoidance strategies are increasing in the group of boys under unsafe conditions, and there is a greater risk that boys will not try their best in school due to fear of failing (Hopland & Nyhus, 2016;Jackson, 2006;Marks, 2000).…”
Section: Previous Researchmentioning
confidence: 99%
“…A constructive learning environment is important due to the fact that boys' academic performance is dependent on the teacher's positive leadership and on the social climate in the classroom (Hopland, & Nyhus, 2016;Francis et al, 2010;Jackson, 2006;Marks, 2000;Patrick et al, 2011). Under insecure conditions, the social climate between the boys toughens and the competition increases, which could lead to more boys exhibiting avoidance strategies (cf.…”
Section: How Do Teachers Perceive Boys' and Girls' Achievements Learmentioning
confidence: 99%